Impact of Energy Consumption and Food Security on Income Inequality: NARDL Approach from Kazakhstan - Kakizhanova, Tolkyn; Sagynbay, Asel; Nurgazy, Shynggys; Andabayeva, Gulmira; Dauliyeva, Galiya (International Journal of Energy Economics and Policy, 2024)
As one of the main socio-economic categories, income inequality has always been a prime focus of many researchers. And Kazakhstan’s income inequality has complex nature. To better understand the functioning of socio-economic mechanisms to find a balance between economic policy and social justice, the relationship of different variables to income inequality is examined. It also helps to develop targeted policies and programs to reduce inequality, thus the poverty. Recently, effect of energy consumption and food safety on income inequality has been under the scrutiny of scientific researchers. These three categories contain many variables. However, due to the availability and breadth of statistical data, the final energy consumption and food import/export ratio were taken into account. We retrieved data from World Bank and it covers the periods from 1996 to 2022. Our study’s aim is to determine the effect of final energy consumption and food security on income inequality. Analyzing data, we used Nonlinear Autoregressive Distributed Lag (NARDL) approach. The NARDL results show that final energy consumption impacts on income inequality positively in both short and long terms, while food security affects negatively on both periods. Results from the model have significant socio-economic and political implications for addressing income inequality.